Hemispheric asymmetry for linguistic prosody: A study of stress perception in Croatian - Mildner, Vesna (Array, 2004)
The aim of this study was to test for possible functional cerebral asymmetry in processing one segment of linguistic prosody, namely word stress, in Croatian. The test material consisted of eight tokens of the word "pas" under a falling accent, varying only in vowel duration between 119 and 185 ms, attached to the end of a frame sentence. The sentence could, depending on the duration of the the vowel, mean "This is a beautiful dog" or "This is a beautiful belt/waist." Each sentence was presented eight times in three dichotic listening conditions (binaural, left ear only, right ear only), in random order. Fourty healthy female right-handers participated in a forced-choice lexical task. For each presented sentence they had to decide whether it referred to the animal (short vowel in the key word) or to the belt/waist (long vowel in the key word).Their oral responses were analyzed in terms of response time and categoricity. No consistent significant differences were found among listening conditions. The responses possibly reflect the nonlateralized activity of subcortical regions or a simultaneous activity of both hemispheres relying on different cues.